From the Economics of Laissez Faire to the Ethics of Libertarianism - Hoppe, Hans-Hermann (MISES: Interdisciplinary Journal of Philosophy, Law and Economics, 2013)
The author shows, from the differences between ethics and the concept of laissez faire libertarian ethics, that the latter not only can be justified by a priori reasoning, but also that no ethical alternative can be justified argumentatively.